A Novel Cutting Method for Face-Hobbed Spiral Bevel Gears Based on Tool Path Modification. Issue 1 (1st January 2022) - Li, Lingzhi; Guo, Wenchao; Yang, Huawei; Mao, Shimin
Abstract: A novel tooth surface design method of face-hobbed spiral bevel gears is proposed, which utilizes a solid cutter without axis tilting through tool path control combining with optimized cutter blade profile to control tooth contact patterns and realize tooth lengthwise chamfering. Firstly, a gear tooth surface generating plan of tool path controlling actively is developed, the mathematical model of the tool path is built, and the equations are given in detail, the determination method of all control parameters is also described. Next, the tooth surface functions of generating gear and machined gear are established based on a mathematic model of the traditional cradle machine tool. Then, the machine setting is also given in concise equations. Finally, the tooth contact analysis is also conducted for a specific gear pair to validate the validity and the reasonability of the new tooth modification method.